Inclusion of a feed premix with lupine, vicia, flaxseed and wheat in the milk replacer for crossbred Holstein male calves - Paredes A., Manuel (2020)
The inclusion of a pre-mix of unconventional ingredients (PM-INC) with lupine, vicia, flaxseed and wheat as part of milk replacer (LR) was evaluated. Twenty-four newborn Holstein male calves, distributed in three treatments were used: T1: whole milk (LE), T2 (LR-LDMC): LR with 80% skim milk (LD) + 20% lard, T3 (LR-LDINC): LR with 75% LD + 25% PM-INC. The LE and LR were supplied from birth to weaning (eight weeks), the starter feed was supplied from the second week and alfalfa hay from the sixth week. No significant differences were observed between treatments for feed consumption, ratio feed/gain, body weight, weight gain, or size. However, a lower cost of weaning calf was found for feeding in the LR-LDINC treatment equivalent to S/. 13.37 less with respect to the treatment LE and S/. 13.51 less with respect to the LR-LDMC treatment. It is concluded that, the Holstein male calf crossed from the high Andean area of Cajamarca satisfactorily responds to the ingest of an LR containing 75% LD + 25% PMINC, in the milk-feeding phase for 56 days.